Manipulating Majorana zero modes on atomic rings with an external magnetic field - Li, Jian; Neupert, Titus; Bernevig, B. Andrei; Yazdani, Ali (Nature communications, 2016)
Non-Abelian quasiparticles have been predicted to exist in a variety of condensed matter systems. Their defining property is that an adiabatic braid between two of them results in a non-trivial change of the quantum state of the system. The simplest non-Abelian quasiparticles—the Majorana bound states—can occur in one-dimensional electronic nano-structures proximity-coupled to a bulk superconductor. Here we propose a set-up, based on chains of magnetic adatoms on the surface of a thin-film superconductor, in which the control over an externally applied magnetic field suffices to create and manipulate Majorana bound states. We consider specifically rings of adatoms and show that they allow for the creation, annihilation, adiabatic motion and braiding of pairs of Majorana bound states by varying the magnitude and orientation of the external magnetic field. Majorana fermions, particles which are their own antiparticles, are predicted to exist in systems combining superconductivity and topologically non-trivial band structure. Here, the authors propose means to create and manipulate such excitations in one-dimensional chains of adatoms on superconducting surfaces.